(untitled) (Journal of Educational Sciences, 2016)
Conducted in the article methodological analysis allows to define methodological approaches to identification of essence of the concept of didactic construction of IT-disciplines and to build its system-active model. Among the General scientific approaches the author identifies systemic, holistic, activity-related and praxiological approaches. Specifically,research (didactic) approaches in the study are personality-activity, competence and technology. These approaches also provide a theoretical basis and tools for construction didactic objectives, content and technologies of teaching IT-disciplines. The author of the levels: philosophical, General scientific, concrete science and technology illustrated the construction of a course on information technology training. The proposed stages of construction disciplines: clarifying the goals of a discipline; definition of psychological-pedagogical and organizational-pedagogical conditions of teaching; clarification of the structure and content of the IT-disciplines; the definition of pedagogical technologies of learning; structuring and meaning of the content; selection (development) of training and methodological support; selection (development) of methods and means of diagnostics;the reflexive stage.